2019
DOI: 10.1108/srj-01-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corporate social responsibility (CSR) health-care services on patients’ satisfaction and loyalty – a case of Bangladesh

Abstract: Purpose Although research on patient satisfaction and loyalty has grown rapidly, the literature on corporate social responsibility (CSR) health care and patient satisfaction and loyalty is scarce. This paper aims to examine the impact of CSR health care on patient satisfaction and loyalty in Bangladesh. Design/methodology/approach A quantitative study was performed, and data were collected using purposive sampling among 195 patients who used CSR health-care services from six public and private hospitals in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“… 23 A quantitative study of 195 patients in 6 public and private hospitals in Bangladesh found that PS had a positive impact on PL to medical industry. 24 Satisfaction can be improved through variables such as reliability, empathy, and responsiveness, and the loyalty of patients will be strongly affected by satisfaction. 25 Abekah-Nkrumah et al 26 found that the ownership of health facility will not directly affect PS and PL.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 23 A quantitative study of 195 patients in 6 public and private hospitals in Bangladesh found that PS had a positive impact on PL to medical industry. 24 Satisfaction can be improved through variables such as reliability, empathy, and responsiveness, and the loyalty of patients will be strongly affected by satisfaction. 25 Abekah-Nkrumah et al 26 found that the ownership of health facility will not directly affect PS and PL.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the results of the study conducted by Dachyar et al (2018) patients' satisfaction affects patient commitment. Hossain et al (2019) found that the satisfaction of patients in Bangladesh had a positive influence on their' commitment to the health-care providers in their study. Permana et al (2019) and Mahendrayana et al (2018) found that patient satisfaction had a positive and significant effect on patient commitment.…”
Section: Resultsmentioning
confidence: 88%
“…CSR is an important tool that helps hospitals understand the societal needs of their community, resulting in higher performance and a better social image [1]. OI, a specific form of social identification, refers to the extent of belonging to different social groups [27].…”
Section: Csr Relationship With Organizational Identification and Employee Attachmentmentioning
confidence: 99%
“…First, CSR describes the relationship between an organization and its community; yet, evidence is scarce on the impact of HCWs' CSR perceptions in the health care sector. Accordingly, it is imperative to examine the impact of employees' CSR perceptions in countries such as Lebanon, where CSR knowledge is overcast [1,11,12].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation